The Impact Of Make Every Minute Count Classroom Management On The Activities Of Class IV Students - Maman Hermawan, Cecep; Rosfiani, Okta; Sheilla, Rani; Nur Elizah, Siti; Hawari, Sulthan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The present study reports the first comprehensive study on the freshwater macroinvertebrates and its habitat preferences in Bilah River, the largest riverin the Northern Sumatra. The riverside is characterized by the presence of anthropogenic and industrial activities which may alter the macroinvertebrate assemblage and biodiversity. Five moon 1, 2, 3 and 4 while group 2 consisted of station 5, 6, 7, 8, 9, and 10. Based on the diversity indices as ecological parameters, the habitat condition in Bilah River is categorized from low to moderately polluted. Spatial patterns in both environmental conditions affecting the macroinvertebrate assemblage was observed using canonical correspondence analysis (CCA) revealed the preferences from each macroinvertebrate species towards environmental conditions This study aims to find out: (1) Population variance of the two groups is the same or homogeneous, (2) Differences in average student learning outcomes, (3) The influence of class management Make Every Minute Count on student learning activity. This research is quantitative research using experimental methods and quasi-experimental design. The research population is the entire student at MI Taufiqurrahman 2 Kukusan which totaled 457 students. The sample technique used is purposive sampling. Research sample of 42 students consisting of class IV A 21 students (experimental) and IV B 21 students (kontrol). The data collection technique uses the lift as the primary instrument. From the test results the instrument obtained a Table R of 0.396 and Cronbach's Alpha of 0.836. The results analysis technique uses the t-test, which compares the two groups' rata-rata. The research findings indicate that: (1) Based on the information available, the significance level (Sig.) is less than 0.198 > 0.05, indicating a similar or homogenous population variation. (2) Based on results showing that the average learning time for the Afterwards Experiment (Make Every Minute Count) was 86,00 and the average deviation was 5,167, as well as the Average Learning Time for the Afterwards Control (Classroom Meeting) was 82,29 and the average deviation was 6,133. It may be observed that there are differences in student learning activity between the